2008
DOI: 10.1037/0097-7403.34.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Amount of training and cue-evoked taste-reactivity responding in reinforcer devaluation.

Abstract: In two experiments, rats received minimal (16) pairings of one auditory conditioned stimulus (CS) cue with a sucrose reinforcer, and extensive (112) pairings of another auditory CS with that reinforcer. After sucrose was devalued by pairing it with lithium chloride in some rats (Devalue groups) but not others (Maintain groups), taste reactivity (TR) and other responses to unflavored water were assessed in the presence of the auditory CSs alone. The minimally-trained CS controlled substantially more evaluative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 41 publications
5
52
0
Order By: Relevance
“…Holland, Lasseter, and Agarwal (2008) recently extended an earlier finding of Holland (1998) in which it was demonstrated that mediated conditioning but not US devaluation effects are affected by the amount of CS-US training trials administered prior to the critical treatment. For instance, Holland, et al (2008) demonstrated that the influence of an auditory cue for sucrose upon the rats’ taste reactivity responses to plain water is diminished as the number of CS-US pairings is increased. However, at the same time, these authors also reported that the number of training trials did not reduce the sensitivity of the auditory-cue-evoked magazine approach response to sucrose devaluation.…”
Section: Nature Of the Ussupporting
confidence: 58%
“…Holland, Lasseter, and Agarwal (2008) recently extended an earlier finding of Holland (1998) in which it was demonstrated that mediated conditioning but not US devaluation effects are affected by the amount of CS-US training trials administered prior to the critical treatment. For instance, Holland, et al (2008) demonstrated that the influence of an auditory cue for sucrose upon the rats’ taste reactivity responses to plain water is diminished as the number of CS-US pairings is increased. However, at the same time, these authors also reported that the number of training trials did not reduce the sensitivity of the auditory-cue-evoked magazine approach response to sucrose devaluation.…”
Section: Nature Of the Ussupporting
confidence: 58%
“…In addition, in both delivery conditions, simple licking responses, characterized by Berridge (2000) as consummatory but nonhedonic, showed moderate but not complete sensitivity to devaluation. Thus, the results of Holland et al's (2008) study suggest that, regardless of reinforcer delivery method, evaluative TR responses are especially sensitive to devaluation, compared to nonevaluative consummatory responses (simple licking), and (with conventional delivery) to appetitive responses (food cup entry).…”
Section: Is Learning S-s or S-r?mentioning
confidence: 82%
“…Consistent with that possibility, Colwill and Rescorla (1990) found nearly complete devaluation of operant lever pressing after training and devaluation with intraoral reinforcer delivery. More recently, Holland, Lasseter and Agarwal (2008) examined consummatory and TR responses in devaluation experiments with either intraoral or conventional (to a recessed cup) delivery of sucrose reinforcers. The food cups were equipped with cameras to permit measuring TR responses in the cup condition as well as the intraoral delivery condition.…”
Section: Is Learning S-s or S-r?mentioning
confidence: 99%
“…However, it is only one exemplar of a wider and long-studied class of revaluation changes in Pavlovian responses that we suggest demand explanation in terms of similar model-based mechanisms, involving stimulus-stimulus associations that preserve the details about the identities of events that have been learned (Dickinson, 1986; Holland, 1990; Holland, Lasseter, & Agarwal, 2008) (Bouton & Moody, 2004; Holland et al, 2008; Rescorla, 1988; Rizley & Rescorla, 1972; Zener & McCurdy, 1939). In all of these, individuals show that they can use learned information about the identity of a UCS that is associated with a particular CS when new information is later added to that CS (for example, developing a taste aversion to an absent UCS, when its associated CS later becomes paired associatively with illness (Holland, 1990).…”
Section: ) Introductionmentioning
confidence: 84%
“…Although we discuss some differences later, there are further similarities between Pavlovian and instrumental effects of extensive training. For instance, it has been observed (Holland et al, 2008) that the predictive capacities of first-order appetitive CSs (which are directly associated with UCSs) are immediately affected by UCS revaluation, whereas second-order CSs (whose associations are established via first order CSs) are less influenced (Holland & Rescorla, 1975; Rescorla, 1973; Rescorla, 1974). Such results suggested that first order CSs establish stimulusstimulus associations (i.e., identity predictions), whereas second order CSs instead directly elicit responses engendered during conditioning (via stimulus-response associations).…”
Section: ) the Algorithmic Levelmentioning
confidence: 99%